Heat Exchangers - ferhat-mohammedfouad (University of Eloued جامعة الوادي, 2025)
Abstract This educational publication provides a comprehensive overview of the principles and applications of heat transfer and heat exchangers, aimed at engineering students and professionals. The work begins with a foundational review of the three modes of heat transfer—conduction, convection, and radiation—illustrated through classical laws such as Fourier’s law, Newton’s law of cooling, and the Stefan–Boltzmann law. It progresses to analytical formulations involving the heat diffusion equation under steady-state and transient conditions, with an emphasis on multidimensional systems. A dedicated chapter explores heat transfer from finned surfaces, discussing fin efficiency and effectiveness in enhancing thermal performance. The text also covers natural and forced convection, supported by key dimensionless numbers (Nusselt, Reynolds, Prandtl, Grashof, Rayleigh) and their role in empirical correlations. The final sections present a detailed study of heat exchangers without phase change, including their configurations (double-tube, plate, shell-and-tube), and performance evaluation using the Log Mean Temperature Difference (LMTD) and Effectiveness–NTU methods. Overall, the booklet integrates theory with engineering applications, equipping readers with practical tools for designing and analyzing heat exchanger systems.
مطبوعة بيداغوجية موجهة لطلبة سنة ولى ماستر هندسة كيمائية
Keywords: Heat Transfer Thermal Conduction Heat Exchangers Fin Efficiency Log Mean Temperature Difference (LMTD) Effectiveness–NTU Method Steady-State and Transient Heat Transfer